1989
DOI: 10.1007/bf01537266
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic motility in canine colon: Responses to feeding and perfusion

Abstract: To further characterize colonic motility in the dog and to examine the effects of intraluminal contents, motor activity in conscious animals was recorded by perfused intraluminal catheters. Animals were studied first with the bowel intact and, later, the colon was fashioned into an isolated loop. In the fasting state, cycles of motility recurred approximately each 30 min. These consisted of sequences of phasic contractions (bursts) that migrated variable distances in either direction; stationary bursts were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…[29][30][31][32] Construction of a diverted total colonic loop with interruption of only luminal continuity failed to change the interdigestive colonic contractile activity in dogs. 9 Shibata et al 33 isolation and extrinsic denervation did not affect regular colonic contractile activity. However, propagation patterns of the colonic contractile activity were not evaluated sufficiently in the small isolated segment.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…[29][30][31][32] Construction of a diverted total colonic loop with interruption of only luminal continuity failed to change the interdigestive colonic contractile activity in dogs. 9 Shibata et al 33 isolation and extrinsic denervation did not affect regular colonic contractile activity. However, propagation patterns of the colonic contractile activity were not evaluated sufficiently in the small isolated segment.…”
mentioning
confidence: 97%
“…In contrast to the upper gastrointestinal tract, the colon always displays very complicated motility patterns such as segmental constrictions, 7 contractions propagating in both orad and aborad directions, [8][9][10] and giant migrating contractions. [10][11][12] In addition, colonic motility is more difficult to study because the MMC seen in the small intestine is not present in the colon.…”
mentioning
confidence: 98%
“…[63][64][65][66][67] Sarna et al 64 reported that the basic pattern of contraction in the canine colon consists of a quiescent state and a contractile state. 64 They defi ned two patterns of contractile activity: colonic migrating motor complexes (CMMC) and colonic non-migrating motor complexes (CNMC).…”
Section: Colorectal Surgerymentioning
confidence: 98%
“…Given their similarities, the dog has been commonly used to study factors impacting motility of the stomach [59], small intestine [60], cecum [61], and colon [62][63][64] and several other gastrointestinal systems/processes, including gastric responses to biopharmaceutics [65], enteral feeding to neonates [66], intestinal cell fuel oxidative metabolism [67], and microbial fermentation [16]. For the remainder of this review, we will highlight the current evidence justifying use of the canine model for studying intestinal health and disease.…”
Section: Canine As Model For Intestinal Health and Diseasementioning
confidence: 98%